Factor H-Related (FHR)-1 and FHR-2 Form Homo- and Heterodimers, while FHR-5 Circulates Only As Homodimer in Human Plasma - van Beek, Anna E.; Pouw, Richard B.; Brouwer, Mieke C.; van Mierlo, Gerard; Geissler, Judy; Ooijevaar-de Heer, Pleuni; de Boer, Martin; van Leeuwen, Karin; Rispens, Theo; Wouters, Diana; Kuijpers, Taco W. (Frontiers in Immunology, 2017)
The complement factor H-related (FHR) proteins are hypothesized to fine-tune the regulatory role of complement factor H (FH) in the alternative pathway of the complement system. Moreover, FHR-1, FHR-2 and FHR-5 have been proposed to be dimers, which further complicates accurate analysis. As FHRs are highly similar among themselves and towards FH, obtaining specific reagents for quantification of serum levels and functional analysis is challenging. In this study, we generated antibodies and developed ELISAs to measure FHR-1, FHR-2 and FHR-5 in serum. We used both recombinant and serum-derived proteins to show that four dimers occur in human circulation: homodimers of FHR-1, FHR-2 and FHR-5, as well as FHR-1/FHR-2 heterodimers. Heterodimers containing FHR-5 were not found. In individuals with homozygous CFHR1 deletions or compound heterozygous CFHR2 missense/nonsense mutations identified in this study, the respective FHR-1 and FHR-2 homo- and heterodimers were absent. Using FRET, we found that recombinant FHR dimers exchange monomers rapidly. This was confirmed ex vivo, using FHR-1 and FHR-2 deficient sera. Of all FHR dimers, FHR-5/5 homodimers demonstrated strong binding affinity towards heparin. Specific ELISAs demonstrated that serum levels of FHR-1/1, FHR-1/2, FHR-2/2 and FHR-5/5 dimers were low compared to FH, which circulates at a 10 - 200 fold molar excess. In summary, FHR-1, FHR-2 and FHR-5 homodimerize, with FHR-1 and FHR-2 forming heterodimers as well, and equilibrate quickly in plasma.